Aerodynamic optimization of the exhaust system of an aft-mounted boundary layer ingestion propulsor - Matesanz García, Jesús; Piovesan, Tommaso; MacManus, David G. (Cranfield University, 2022)
Novel aircraft propulsion configurations require a greater integration of the propulsive system with the airframe. As a consequence of the closer integration of the propulsive system, higher levels of flow distortion at the fan face are expected. This distortion will propagate through the fan and penalize the system performance. This will also modify the exhaust design requirements. Hence, the aerodynamic design of the exhaust system becomes crucial to reduce the penalties of the distortion on the system performance. This work defines a methodology for the optimization of exhaust systems for novel embedded propulsive systems. As the case study a 2D axisymmetric aft mounted annular boundary layer ingestion (BLI) propulsor is used. An automated CFD approach is applied with a parametric definition of the design space. A throughflow body force model for the fan is implemented and validated for 2D axisymmetric and 3D flows. A multi-objetive optimization based on evolutionary algorithms is used for the exhaust design. A maximum benefit of approximately 0.32% on the total aircraft required thrust was observed by the application of compact exhaust designs. Furthermore, for the embedded system, is observed that the design of the compact exhaust and the nacelle afterbody have a considerable impact on the aerodynamic performance. To the author’s knowledge, this is the first detailed optimization of an exhaust system on an annular aft-mounted BLI propulsor.